Economic Performance under NAFTA : A Firm-Level Analysis of the Trade-Productivity Linkages - De Hoyos, Rafael E.; Iacovone, Leonardo (2012)
Did the North American Free Trade Agreement make Mexican firms more productive? If so, through which channels? This paper addresses these questions by deploying an innovative microeconometric approach that disentangles the various channels through which integration with the global markets (via international trade) can affect firm-level productivity. The results show that the North American Free Trade Agreement stimulated the productivity of Mexican plants via: (1) an increase in import competition and (2) a positive effect on access to imported intermediate inputs. However, the impact of trade reforms was not identical for all integrated firms, with fully integrated firms (i.e. firms simultaneously exporting and importing) benefiting more than other integrated firms. Contrary to previous results, once self-selection problems are solved, the analysis finds a rather weak relationship between exports and productivity growth.